Regional brain blood flow in man during acute changes in arterial blood gases - Willie, C. K.; Macleod, D. B.; Shaw, A. D.; Smith, K. J.; Tzeng, Y. C.; Eves, N. D.; Ikeda, K.; Graham, J.; Lewis, N. C.; Day, T. A.; Ainslie, P. N. (The Journal of physiology, 2012)
Key points • The partial pressures of arterial carbon dioxide () and oxygen () has a marked influence on brain blood flow. • It is unclear if the larger brain arteries are also sensitive to changing and and if different areas of the brain possess different sensitivities. • We separately altered and and measured the diameter and blood flow in the main arteries delivering blood to the cortex and brainstem. • During alterations in and , the large arteries changed diameter and blood flow to the brainstem changed more than that to the cortex. • These findings change the basis of our understanding of brain blood flow control in humans. Despite the importance of blood flow on brainstem control of respiratory and autonomic function, little is known about regional cerebral blood flow (CBF) during changes in arterial blood gases. We quantified: (1) anterior and posterior CBF and reactivity through a wide range of steady‐state changes in the partial pressures of CO2 () and O2 () in arterial blood, and (2) determined if the internal carotid artery (ICA) and vertebral artery (VA) change diameter through the same range. We used near‐concurrent vascular ultrasound measures of flow through the ICA and VA, and blood velocity in their downstream arteries (the middle (MCA) and posterior (PCA) cerebral arteries). Part A (n= 16) examined iso‐oxic changes in , consisting of three hypocapnic stages (=∼15, ∼20 and ∼30 mmHg) and four hypercapnic stages (=∼50, ∼55, ∼60 and ∼65 mmHg). In Part B (n= 10), during isocapnia, was decreased to ∼60, ∼44, and ∼35 mmHg and increased to ∼320 mmHg and ∼430 mmHg. Stages lasted ∼15 min. Intra‐arterial pressure was measured continuously; arterial blood gases were sampled at the end of each stage. There were three principal findings. (1) Regional reactivity: the VA reactivity to hypocapnia was larger than the ICA, MCA and PCA; hypercapnic reactivity was similar. With profound hypoxia (35 mmHg) the relative increase in VA flow was 50% greater than the other vessels. (2) Neck vessel diameters: changes in diameter (∼25%) of the ICA was positively related to changes in (R2, 0.63 ± 0.26; P < 0.05); VA diameter was unaltered in response to changed but yielded a diameter increase of +9% with severe hypoxia. (3) Intra‐ vs. extra‐cerebral measures: MCA and PCA blood velocities yielded smaller reactivities and estimates of flow than VA and ICA flow. The findings respectively indicate: (1) disparate blood flow regulation to the brainstem and cortex; (2) cerebrovascular resistance is not solely modulated at the level of the arteriolar pial vessels; and (3) transcranial Doppler ultrasound may underestimate measurements of CBF during extreme hypoxia and/or hypercapnia.